Increased Risk of Dementia in Patients with Mild Traumatic Brain Injury: A Nationwide Cohort Study - Lee, Yi-Kung; Hou, Sheng-Wen; Lee, Ching-Chih; Hsu, Chen-Yang; Huang, Yung-Sung; Su, Yung-Cheng (PloS one, 2013)
It is known that the risk of dementia in patients with moderate to severe traumatic brain injury (TBI) is higher. However, the relationship between mild traumatic brain injury (mTBI) and dementia has never been established. We investigated the incidences of dementia among patients with mTBI in Taiwan to evaluate if there is higher risk compared with general population. We utilized a sampled National Health Insurance (NHI) claims data containing one million beneficiaries. We followed all adult beneficiaries from January 1, 2005 till December 31, 2009 to see if they had been diagnosed with dementia. We further identify patients with mTBI and compared their risk of dementia with the general population. We identified 28551 patients with mTBI and 692382 without. After controlled for age, gender, urbanization level, socioeconomic status, diabetes, hypertension, coronary artery disease, hyperlipidemia, history of alcohol intoxication, history of ischemic stroke, history of intracranial hemorrhage and Charlson Comorbidity Index Score, the adjusted hazard ratio is 3.26 (95% Confidence interval, 2.69-3.94). TBI is an independent significant risk factor of developing dementia even in the mild type.